2011
DOI: 10.15835/nbha3916101
|View full text |Cite
|
Sign up to set email alerts
|

Auxin Control in the Formation of Adventitious Roots

Abstract: Adventitious rooting is a complex process and a key step in the vegetative propagation of economically important woody, horticultural and agricultural species, playing an important role in the successful production of elite clones. The formation of adventitious roots is a quantitative genetic trait regulated by both environmental and endogenous factors. Among phytohormones, auxin plays an essential role in regulating roots development and it has been shown to be intimately involved in the process of adventitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 120 publications
(132 reference statements)
2
67
0
13
Order By: Relevance
“…In a biochemical study to elucidate IBA mode of action in various plants and the use of Arabidopsis-IBA mutants, it was found that IBA acts mainly through its conversion to IAA. However, some scientific findings indicated that IBA exert a hormonal action as an auxin (Pop, Pamfil, & Bellini, 2011).…”
Section: Application Of Iba Alonementioning
confidence: 99%
“…In a biochemical study to elucidate IBA mode of action in various plants and the use of Arabidopsis-IBA mutants, it was found that IBA acts mainly through its conversion to IAA. However, some scientific findings indicated that IBA exert a hormonal action as an auxin (Pop, Pamfil, & Bellini, 2011).…”
Section: Application Of Iba Alonementioning
confidence: 99%
“…El AIB es más estable y efectivo que AIA para la inducción de raíces laterales, además puede ser convertido a AIA en los peroxisomas por β-oxidación (Zolman et al 2000, Woodward & Bartel 2005. Según Pop et al (2011), el AIB puede potenciarse con los contenidos de AIA endógeno, en este caso puede ser explicada por una mayor estabilidad, diferentes metabolismos, diferencia en el transporte y la conversión del AIB en AIA, esta interacción AIB-AIA difiere entre las especies, lo que también puede reflejarse entre clones distintos de una misma especie (Ludwig-Müller et al 2005, Saini et al 2013.…”
Section: Discussionunclassified
“…Independiente del tratamiento utilizado, todos los microtallos enraizados formaron un callo basal de donde emitían raíces adventicias. La formación de callo basal es muy frecuente en esquejes y es provocado por una mayor concentración de auxinas en la zona de la herida (Pop et al 2011), sin embargo las raíces adventicias en otras especies pueden ser emitidas desde puntos del tallo distinto al callo basal, incluso el callo basal se puede desarrollar después de la emisión de las raíces. Al respecto, Štefančič et al (2005) observaron en portainjertos de Prunus 'GiSelA5' que los sistemas radiculares desarrollados a partir de un callo basal eran de menor calidad.…”
Section: Discussionunclassified
See 2 more Smart Citations